Cuidado de enfermería en la prevención de úlceras por presión en adultos mayores del servicio de medicina interna de un hospital local, Chiclayo 2019 - Cienfuegos Da Silva, Karen Paola (2020)
Objective: Describe and analyze nursing care in the prevention of pressure ulcers in older adults from the internal medicine service of a local hospital. Method: Qualitative research with a case study methodological approach. The study subjects were made up of 24 participants (12 nursing professionals and 12 family caregivers of elderly patients), who met selection criteria; the size of the sample was determined by criteria of saturation and redundancy, non-probabilistic sampling for convenience. To obtain data, the semi-structured interview was applied, prepared by the researcher and validated by an expert judgment, taking into account criteria of scientific rigor and ethical principles. Main results: Three categories were obtained: A) Preventive care of pressure ulcers: changes of positions, skin care, massages, support measures B) Education of the family caregiver for their collaboration in the prevention of pressure ulcers C) Reuse of supplies before limitations for preventing pressure ulcers. Conclusion: The nursing professional recognizes the importance of prevention measures and their implementation, since they are the only tools used by the staff to avoid the appearance of pressure ulcers. Considering teamwork with the technical staff and the family caregiver, who perform position changes, massages, and support measures, refers to the lack of tools that are necessary in a certain service and therefore essential to provide care quality.